ANALISIS MINAT REMAJA STABAT TERHADAP TABUNGAN MABRUR JUNIOR PADA BANK SYARIAH INDONESIA KCP STABAT - M. Guffar Harahap; Mery Handayani Nasution (Jurnal Ekonomi Rabbani, 2021)
The momentum of Hajj for Muslims has its own meaning, apart from being a religious ritual in the last pillars of Islam, Hajj has a moral, spiritual, and intellectual spirit for those who perform it. So that the pilgrimage makes a significant contribution in the process of changing society for the better. The problem is how is the interest of stabat teenagers towards junior mabrur savings at Bank Syariah Indonesia KCP Stabat?. The purpose of this study was to find out how much interest the youth in Stabat had on the junior mabrur savings product at Bank Syariah Indonesia KCP Stabat and find out who influences the interest of Stabat youth. The method used is descriptive qualitative method. The data used is primary data in the form of interviews with BOSM Bank Syariah Indonesia KCP Stabat and secondary data. The results showed that parents were the driving factor for teenagers' interest in junior mabrur savings. For this reason, Bank Syariah Mandiri needs a strategy to increase youth's interest in junior mabrur savings.